2000
DOI: 10.1017/s1355838200991519
|View full text |Cite
|
Sign up to set email alerts
|

Selective importation of RNA into isolated mitochondria from Leishmania tarentolae

Abstract: All mitochondrial tRNAs in kinetoplastid protozoa are encoded in the nucleus and imported from the cytosol. Incubation of two in vitro-transcribed tRNAs, tRNA Ile (UAU) and tRNA Gln (CUG), with isolated mitochondria from Leishmania tarentolae, in the absence of any added cytosolic fraction, resulted in a protease-sensitive, ATP-dependent importation, as measured by nuclease protection. Evidence that nuclease protection represents importation was obtained by the finding that Bacillus subtilis pre-tRNA Asp was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
58
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 54 publications
6
58
0
Order By: Relevance
“…In all other cases known, tRNA import into mitochondria is an ATPrequiring process (8,21,23,24). We have tested the ATP requirements for tRNA Gln import into rat mitochondria and showed that import also requires ATP (Fig.…”
Section: In Vitro Import Into Mammalian Mitochondria Does Not Requirementioning
confidence: 99%
See 4 more Smart Citations
“…In all other cases known, tRNA import into mitochondria is an ATPrequiring process (8,21,23,24). We have tested the ATP requirements for tRNA Gln import into rat mitochondria and showed that import also requires ATP (Fig.…”
Section: In Vitro Import Into Mammalian Mitochondria Does Not Requirementioning
confidence: 99%
“…This antibiotic is known to collapse the membrane potential ⌬⌿ in the presence of potassium ions. Even when valinomycin is added in vast excess (100 times the concentration required to collapse ⌬⌿ in the presence of potassium chloride) (21), it has no effect on the tRNA import efficiency in rat mitochondria (Fig. 6C, compare lanes 1-4 with lane 8).…”
Section: Import Of Trna Into Mammalian Mitochondria Is Distinct From mentioning
confidence: 99%
See 3 more Smart Citations